Perlindungan Hukum Atas Terhadap Peraturan Kebijakan (Beleidsregel) - Murlinus Murlinus (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Discretionary regulations are not a new phenomenon in the administration of government in Indonesia. Wisdom regulations arise due to the needs of the society that continue to develop, requiring the government to take a quick legal action, even overriding the principle of legality or also known as wetmatigheid van bestuur. Because the ruler has extraordinary authority, administrative law functions to provide legal protection for the people for the actions of the ruler by filing a lawsuit to the court. Legal protection for the people from government legal actions is a juridical means in the state of law to prevent or recover losses experienced by the people as a result of legal acts of the government that cause losses to the people.